Marked disparity in regional and transmural cardiac mechanics in the athlete's heart - Stewart, G. M.; Chan, J.; Kane, G. C.; Johnson, B. D.; Balmain, B. N.; Yamada, A.; Shiino, K.; Haseler, L. J.; Sabapathy, S. (Medicine & Science in Sports & Exercise, 2020)
Introduction :Regional heterogeneity of the human heart plays an important role in left ventricular (LV) and right ventricular (RV) function and may contribute to enhanced myocardial efficiency in the athlete`s heart.